A hybrid elastomeric foam-core/solid-shell spherical structure for enhanced energy absorption performance. (15th August 2016) - Yang, Weizhu; Yue, Zhufeng; Xu, Baoxing
Abstract: Energy absorption structures have been pursued to protect personnel and infrastructures over the last few decades. In this study, a novel hybrid foam-core/solid-shell spherical (FSS) structure is presented and investigated. The internal foam core inherits merits of large deformation from conventional foam structures and the introduction of the external thin solid shell is to reach high strength and delay deformation further, thereby achieving high energy absorption efficiency in FSS structures. Theoretical models are developed to characterize elastic modulus and buckling behavior of FSS structures under a compressive loading, and are verified through extensive finite element analysis (FEA). Typical deformation mechanisms are revealed by addressing competition of buckling deformation of the foam core and solid shell, and are identified through the proposed theoretical models. Further, the energy absorption efficiency is proposed to optimize the specific energy absorption density and critical triggering force of activating energy absorption, and is correlated with deformation mechanism and geometric parameters of FSS structures. Both numerical and theoretical analyses show that the employment of a thin solid shell surrounding the foam structures will enhance the energy absorption efficiency with high capability and safe comfort. The present study is expected to provide a useful guideline for a hybrid design of future energy absorption structures with unprecedented performance.